Quantitative Structure activity relationship and risk analysis of some pesticides in the cattle milk - Faqir Muhammad*, Ijaz Javed, Masood Akhtar1, Zia-ur-Rahman, Mian Muhammad Awais1, Muhammad Kashif Saleemi2 and Muhammad Irfan Anwar3 (Pakistan Veterinary Journal, 2012)
Milk of cattle was collected from various localities of Faisalabad, Pakistan. Pesticides concentration was determined by HPLC using solid phase microextraction. The residue analysis revealed that about 40% milk samples were contaminated with pesticides. The mean±SE levels (ppm) of cyhalothrin, endosulfan, chlorpyrifos and cypermethrin were 0.38±0.02, 0.26±0.02, 0.072±0.01 and 0.085±0.02, respectively. Quantitative structure activity relationship (QSAR) models were used to predict the residues of unknown pesticides in the milk of cattle using their known physicochemical properties such as molecular weight (MW), melting point (MP), and log octanol to water partition coefficient (Ko/w) as well as the milk characteristics such as pH, % fat, and specific gravity (SG) in this species. The analysis revealed good correlation coefficients (R2 = 0.91) for cattle QSAR model. The coefficient for Ko/w for the studied pesticides was higher in cattle milk. Risk analysis was conducted based upon the determined pesticide residues and their provisional tolerable daily intakes. The daily intake levels of pesticide residues including cyhalothrin, chlorpyrifos and cypermethrin in present study were 3, 11, 2.5 times higher, respectively in cattle milk. This intake of pesticide contaminated milk might pose health hazards to humans in this locality.